The Digital Picture as Tools for Teaching Young Learners - Kumalasari, Cyintia (JADEs Journal of Academia in English Education, 2023)
Teaching for young learners is more challenging since the characteristics of young learners are quite different from adults. Younger learners are growing up by technology and it has been integrated with their lives. They feel comfortable and confident on using it. The purpose of this study is to examine the teachers’ perception on learning English through technology and to identify the challenges. This study used qualitative descriptive research to perceive the use of technology in teaching young learner including the challenges and to obtain more conclusions, the researcher made an depth interview with a teacher in one of primary school. The results of the research showed that the teachers are mostly agreeing to teach English for young learners by using technology, including digital picture, games, and songs. For the challenges, the teachers faced the lack of students’ concentration and difficulties in saying some words because of mother tongue. This is happened because the students are lack of exposure to English outside classroom. To overcome these challenges, the teacher should be creative making a pleasant classroom atmosphere, actively engaging students to speak English in the classroom and do self-reflection.